Polyculture of tiger shrimp and carps in hardwater seasonal ponds - Athithan, S; Ramanathan, N (Indian Journal of Fisheries, 2011)
Experiments were carried out to assess the growth of tiger shrimp (Penaeusmonodon) and carps under polyculture practice particularly in hardwater seasonalponds. The growth of tiger shrimp and carps were recorded for a periodof 110 and 180 days respectively during December, 2002 to May, 2003. Thegrowth rate of Penaeus monodon and carps under polyculture practice were32g and 298g respectively. The production of shrimp and carps registered underpolyculture practice were 25.750 kg/0.1 ha/110 days (a low stocking densityof 1.5 nos/m2 ) and 135.450 kg/0.1 ha/180 days respectively.